Acute Aerobic Exercise Based Cognitive and Motor Priming: Practical Applications and Mechanisms - Moriarty, Terence A.; Mermier, Christine; Kravitz, Len; Gibson, Ann; Beltz, Nicholas; Zuhl, Micah (Frontiers in Psychology, 2019)
Acute exercise stimulates brain regions involved in motor and cognitive processes. Recent research efforts have explored the benefits of aerobic exercise on brain health and cognitive functioning with positive results reported for both healthy and neurocognitively impaired individuals. Specifically, exercise positioned near therapeutic (both behavioral and physical) activities may enhance outcomes associated with treatment outcomes (e.g., depression or motor skill) through neural plasticity promoting mechanisms (e.g., increased brain flow and oxygenation). This approach has been termed “exercise priming” and is a relatively new topic of exploration in the fields of exercise science and motor control. The authors report on physiological mechanisms that are related to the priming effect. In addition, parameters related to the exercise bout (e.g., intensity, duration) and the idea of combining exercise and therapeutic rehabilitation are explored. This exercise-based priming concept has the potential to be applied to many areas such as education, cognitive therapy, and motor rehabilitation.